Stabilization of a nonlinear Euler-Bernoulli viscoelastic beam subjected to a neutral delay - Lakehal Ibrahim; Benterki Djamila; Zennir Khaled (Theoretical and Applied Mechanics)
An approach is implemented in this article to analyze the decay rate of nonlinear beams according to the Euler–Bernoulli equation in the context of rheological viscoelastic damping deformations taking into account the neutral type delay. The interaction between viscoelastic and neutral type delays is discussed as our main aim to support a rapidly developing literature. Using the energy method and constructing an appropriate Lyapunov functional, under certain conditions on the kernel and neutral delay terms, we show that despite the destructive nature of delays in general, a very general decaying energy for the problem was obtained.